Mangrove Ecotourism as an Education and Learning Facility - Ni Nyoman Sri Putu Verawati; Agil Al Idrus (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This study investigates the educational benefits of mangrove tourism on Gili Sulat, an uninhabited island designated as an Aquatic Tourism Park in Lombok, Indonesia. The study is exploratory research. The research sample was determined purposively, they were 10 fifth-semester Biology Education students engaged in practicums on Gili Sulat. Through a questionnaire and interview sessions, the study explores the students' perceptions and experiences regarding the educational aspects of mangrove ecotourism. Perception data was analyzed qualitatively. The findings reveal that the primary motivation for the students' visit was education and learning, emphasizing the unique ecosystem's allure. The students demonstrated a nuanced understanding of the mangrove ecosystem's role in protecting coastal environments and expressed heightened inspiration for environmental protection. Their suggestions for improvement, such as species name boards, and the willingness to revisit Gili Sulat for educational activities underscore the enduring impact of mangrove ecotourism on fostering environmental awareness and responsibility. The study contributes to the discourse on the educational potential of ecotourism, particularly in the context of mangrove ecosystems, advocating for the continued promotion and preservation of such destinations as invaluable educational resources.